IoT-Based Solar Energy - Sekudan, Ericka Ensimau; Azhar, Ahmad Mirza; Azahar, Kaiyisah Baiduri (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Problems with a shortage of electricity often occur, especially in a rural area, which makes it difficult to do daily work and makes it difficult to communicate with outsiders. Problems with a shortage of electricity can affect the daily activities of residents, especially in rural areas, and can pose risks in the event of emergencies such as illnesses that require mechanical treatment. If this problem persists it could be detrimental to the population who do not have electricity. Electricity is very important as it can make it easier for people to do the work and for the people in the interior to get information. Problems with a shortage of electricity can affect communication networks such as the internet, radio waves, mobile phone lines and so on. In the current state of technology development, the creation of technologies that can solve this problem must be done and referred to as Solar Energy. It is an IoT research that absorbs energy from the sun to produce electricity in every home. The movement of this research can be controlled manually by using a mobile phone connected to the internet and also controlled automatically by the direction of sunlight. With this, updates from users are a must. This meets the user's need for a device that can be used continuously.